(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The aim of this study was to evaluate, in the field, the soil respiration and bulk density under conventional and organic farming plots. The evaluations were made in different plots established as conventional farming system and organic farming system with six, nine, twelve, fifteen, eighteen and twenty one months old. Plots were replicated four times and in each subplot were evaluated soil respiration, bulk density and porosity. The soil respiration was significantly greater in organic farming system with fifteen, eighteen and twenty-one months old as compared with conventional farming. Soil bulk density decreased fifteen months after adoption of organic system. The results showed that the adoption of practices in organic farming plots increases microbial activity and decreases soil bulk density over time.